Moving Business Rules From System Models to Business Rules Repository - Vasilecas, Olegas; lebedys, Evaldas (INFOCOMP Journal of Computer Science, 2006)
The paper discusses business systems modelling and information systems development from business rules perspective. The way business rules influence different system models is analysed in the paper. The paper presents a method to create a whole business rules system model without separating business rules from models representing other aspects of the system: system structure, behaviour, actor’s roles etc. The paper briefly discusses business rules represented in UML use case diagrams. A software system implementing the proposed method is presented in the paper. The paper shortly presents the results of the experiment performed on a use case model of a textile factory.